Reciprocal Interaction between Two Cellular Proteins, Purα and YB-1, Modulates Transcriptional Activity of JCV(CY) in Glial Cells - Safak, Mahmut (American Society for Microbiology, 1999)
Cross communication between regulatory proteins is an important event in the control of eukaryotic gene transcription. Here we have examined the structural and functional interaction between two cellular regulatory proteins, YB-1 and Purα, on the 23-bp sequence element derived from the enhancer-promoter of the human polyomavirus JCV. YB-1 and Purα are single-stranded DNA binding proteins which recognize C/T- and GC/GA-rich sequences, respectively. Results from band shift studies demonstrated that while both proteins interact directly with their DNA target sequences within the 23-bp motif, each protein can regulate the association of the other one with the DNA. Affinity chromatography and coimmunoprecipitation provide evidence for a direct interaction between Purα and YB-1 in the absence of the DNA sequence. Ectopic expression of YB-1 and Purα in glial cells synergistically stimulated viral promoter activity via the 23-bp sequence element. Results from mutational studies revealed that residues between amino acids 75 and 203 of YB-1 and between amino acids 85 and 215 of Purα are important for the interaction between these two proteins. Functional studies with glial cells indicated that the region within Purα which mediates its association with YB-1 and binding to the 23-bp sequence is important for the observed activation of the JCV promoter by the Purα and YB-1 proteins. The results of this study suggest that the cooperative interaction between YB-1 and Purα mediates the synergistic activation of the human polyomavirus JCV genome by these cellular proteins. The importance of these findings for cellular and viral genes which are regulated by Purα and YB-1 is discussed.